Pengaruh Kompetensi SDM dan Penerapan Standar Akuntansi terhadap Kualitas Laporan Keuangan: Peran Moderasi Teknologi Informasi - Baquita M. G. Pereira; Baldric Siregar; Miswanto Miswanto; Frasto Biyanto (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This study aims to examine the influence of human resource competence and the implementation of accounting standards on the quality of financial statements and to investigate the moderating role of information technology. A quantitative survey approach was employed involving 228 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The findings indicate that human resource competence and the implementation of accounting standards have positive and significant effects on the quality of financial statements. Both variables also positively influence information technology, while information technology has a significant positive effect on financial statement quality. However, information technology does not significantly moderate the relationship between the implementation of accounting standards and financial statement quality. These findings suggest that improving financial statement quality is primarily driven by competent human resources, proper implementation of accounting standards, and the direct utilization of information technology rather than by its moderating effect.